How to Enhance Government Trust and Social Cohesion: Evidence From China - Fan, Juan; Zheng, Hanyi; Liang, Wenhui (Frontiers in Psychology, 2022)
Governments’ impression management behaviors are becoming increasingly common. Under this context, this study empirically analyzes the relationship between governments’ impression management behavior, citizens’ government trust and social cohesion by using questionnaire data based on social psychology theories. The conclusion shows that governments’ impression management behaviors positively affect citizens’ government trust and social cohesion. Government trust plays a mediating role between impression management behaviors and social cohesion, and citizens’ education levels positively moderate the relationship between governments’ impression management and citizens’ government trust, i.e., the higher the education level, the stronger the positive effect of governments’ impression management on citizens’ government trust. The findings of the study will provide significant references for the self-presentation of government information, citizens’ government trust and the improvement of social cohesion.